PENGARUH KUALITAS PELAYANAN, FASILITAS, DAN CITRA TERHADAP KEPUASAN PASIEN RAWAT JALAN DI UPT PUSKESMAS PARIGI - Sudaryanto, Sudaryanto; Erliyanti, Risna (PRIMA EKONOMIKA, 2022)
This study aims to determine: 1. The effect of service quality on patient satisfaction at UPT Puskesmas Parigi, 2. Effect of facilities on patient satisfaction at UPT Puskesmas Parigi, 3. Effect of image on patient satisfaction at UPT Puskesmas Parigi. The type of research used in this research is quantitative research. In this study using a sample of 100 respondents. The sample collection technique used is non-probability sampling. Testing the instrument in this study is a test of validity and reliability test. Data collection techniques using a questionnaire with alternative answers using a Likert scale. The analysis technique uses descriptive analysis, multiple linear regression analysis with t test and classical assumption test. The results showed that: 1) the quality of service (X1) showed a value of 4.561 which was greater than 1.984 (). partially the quality of service has a significant effect on patient satisfaction (Y) outpatient at UPT Puskesmas Parigi, 2) the facility (X2) shows the value of the facility (X2) of 2,922 which is greater than 1,984 (). partially the facility has a significant effect on patient satisfaction (Y) outpatient at UPT Puskesmas Parigi, 3) the image (X3) shows the image value (X2) of 2,966 which is greater than 1,984 () partially the image has a significant effect on patient satisfaction (Y) outpatient At UPT Puskesmas Parigi, the coefficient of determination ( ) indicates that the Adjusted R Square value of 0.652 or 65.2% of patient satisfaction is influenced by patient satisfaction, while the remaining 34.8% is influenced by other variables studied in this study. Keywords: Patient Satisfaction, Service Quality, Facilities, Image